Hemorrhagic Transformation in Ischemic Moyamoya Disease: Clinical Characteristics, Radiological Features, and Outcomes - Lu, Junlin; Li, Zelin; Zhao, Yuanli; Chen, Xiaolin; Shi, Guangchao; Zhao, Jizong (Frontiers in Neurology, 2020)
Objective Hemorrhagic transformation (HT) in ischemic moyamoya disease (MMD), reasonably defined as hemorrhage events in patients with ischemic onset manifestation, leads to a poor outcome. This study aims to reveal factors associated with HT in patients with ischemic onset manifestation and to assess the outcome of these patients. Methods A total of 683 surgically managed patients with onset ischemic manifestation were included. The clinical variables of the HT and non-HT groups were compared, and risk factors were analyzed using logistic regression analysis. Recurrent stroke events (including hemorrhagic and ischemic) during the follow-up were documented. The cumulative incidence rate of stroke events was generated via Kaplan-Meier survival analysis. Outcomes were compared between HT and non-HT groups, using propensity-score analysis to account for between-group differences in baseline characteristics. Results Of 683 patients surgically treated in the overall cohort, 29 (4.3%) were classified as cases of HT. The majority manifestation of these patients was transient ischemic attack. Multivariate analysis showed that the normal cerebral perfusion according to the CT perfusion was identified as factors associated with HT (OR 13.464, 95% CI 3.529–51.363, p<0.001). Patients who occurred HT had a worse outcome than patients without HT. Conclusions HT in adult ischemic MMD is a rare phenomenon, but it is strongly associated with increased disability rates and mortality. The normal cerebral perfusion is a possible risk factor associated with HT in adult ischemic MMD. Recognition of HT in adult ischemic MMD may contribute to an improved outcome.